An Analysis of Alternative Interperiod Tax Allocation Methods for Financial Reporting Purposes - Górowski, Ireneusz (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
The article analyses deferred tax allocation procedures in an important area of the contemporary accounting standards. The domestic and international standards solutions are similar, while the theory of accounting offers a range of alternative solutions. The article considers the concepts of full and partial allocation, liability method, deferred tax method, and the pros and cons of the balance sheet and income statement approach. The evaluation identifies the areas of coherence with current accounting standards and theory. It also points out those aspects which might be suitable for re-evaluation in the context of the accounting standards objectives.